The relationship between Learning Interest and Learning Autonomy of the Students of SMP Negeri 10 Yogyakarta - Budi Astuti; Andika Ari Saputra (Universitas Ahmad Dahlan, 2018)
The present study aimed to discover the relationship between Learning Interest and Learning Autonomy of the Students of SMP Negeri 10 Yogyakarta. This study was categorized into correlational and ex post facto study. The population of the study was all students of SMP Negeri 10 Yogyakarta (507 students), the sample of the study was 253 students; they were selected by using proportional stratified random sampling.Â The data were collected using learning interest scale and learning autonomy scale. The data were analyzed using wilcoxon signed rank test, the p result was 0.740 for learning interest and p=0.744 for learning autonomy. The result of the study showed that there was a relationship between Learning Interest and Learning Autonomy of the Students of SMP Negeri 10 Yogyakarta by 0.327, the 5% Ts probability score was 0.000 (p <0.05). The result of the present study can be used as a picture for the school counselor in providing a service that suits the studentsâ€™ learning interest and learning autonomy.